2021
DOI: 10.1097/oi9.0000000000000148
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of long bone fracture healing in Samburu County Referral Hospital (Kenya): the squat and smile challenge

Abstract: Background: The burden of musculoskeletal trauma is increasing in low- and middle-income countries. Due to the low clinical follow-up rates in these regions, the Squat-and-Smile test (S&S) has previously been proposed as a proxy to assess bone healing (BH) capacity after surgery involving bone fractures. This study deals with various aspects of using S&S and bone radiography examination to obtain information about an individual's ability to recover after a trauma. In summary, we performed the S&S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
(53 reference statements)
1
2
0
Order By: Relevance
“… 24 Functional healing has been assessed using the S&S test, the patient's ability to perform an unassisted active knee range-of-motion squat, which we have shown to indicate earlier healing compared with radiographic evaluation, but its utility as a measure of healing is controversial. 17 , 20 , 25 , 26 Of the 84 patients in our cohort who had an S&S test, 83.3% of them were considered functionally healed which is similar to Scuito et al 17 who found 80.2% of their 89 patient cohort with femoral fractures were able to pass the S&S test at 24 weeks. Our findings comparing S&S with radiographic healing showed a significant correlation between the 2 tests which may add validity to the S&S examination.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“… 24 Functional healing has been assessed using the S&S test, the patient's ability to perform an unassisted active knee range-of-motion squat, which we have shown to indicate earlier healing compared with radiographic evaluation, but its utility as a measure of healing is controversial. 17 , 20 , 25 , 26 Of the 84 patients in our cohort who had an S&S test, 83.3% of them were considered functionally healed which is similar to Scuito et al 17 who found 80.2% of their 89 patient cohort with femoral fractures were able to pass the S&S test at 24 weeks. Our findings comparing S&S with radiographic healing showed a significant correlation between the 2 tests which may add validity to the S&S examination.…”
Section: Discussionsupporting
confidence: 86%
“…While nonunion can be assessed for radiographic, clinical, or functional healing, this study focused primarily on radiographic and functional healing. 14,17,18 Radiographic union and nonunion have been reliably assessed using the mRUST score. [13][14][15]19 This study found the union rate for transverse femur fractures to be 61.0% based on mRUST score at a minimum of 9-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation